(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2013)
This study is conducted to develop the aerobic granules for domestic wastewater treatment application in a hot climate (specifically at a temperature of 30oC). A 3 L laboratory scale, slightly modified sequencing batch reactor (SBR) was built and used for the experimental study. The observation shows that after 90 d of the SBR operation, stable aerobic granules with an average size of 1.1 mm were formed at 30oC (fed with acetate). The formation of the aerobic granules is also achievable with a complex influent (pre-treated sewage) after operating the SBR system for 125 days and the average size of the granules from this operation was found to be 0.8 mm. In addition, the results also proved that high temperature (30oC) did not affect the development of stable, dense and good settle able granules; thus making the granular sludge SBR system an effective technology for wastewater treatment in hot climates.